Multiple Sclerosis Presenting with Facial Twitching (Myokymia and Hemifacial Spasms) - Risha Hertz; James Espinosa; Alan Lucerna; Doug Stranges (Case Reports in Neurological Medicine)
Multiple sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system. The etiology is insufficiently understood. Autoimmune, genetic, viral, and environmental factors have been hypothesized. MS is twice as common in women as in men between the ages of 20 and 50 years. There is no known cure for MS. Current medical treatment helps to prevent new attacks and improve function after an attack. MS is diagnosed by physical examination, diagnostic imaging, and examination of cerebral spinal fluid. The most common physical signs and symptoms of MS include constitutional symptoms, muscle weakness, motor and autonomic spinal cord symptoms, paresthesias, and vision changes. Here we present a case of MS diagnosed in a 33-year-old male with facial myokymia of left eyelid, which progressed to left hemifacial spasm. This is an unusual presentation for multiple sclerosis. An awareness of this presentation not only may lead to an earlier diagnosis in some patients but can be a sign of relapse in patients with established multiple sclerosis.